2011
DOI: 10.5586/asbp.2010.008
|View full text |Cite
|
Sign up to set email alerts
|

The hybrid origin of Calamagrostis ×gracilescens (Poaceae) in Poland inferred from morphology and AFLP data

Abstract: The morphology of Calamagrostis canescens and C. stricta recorded in the Ma³opolska Upland (the vicinity of Zbijów Ma³y, ca. 10 km northeast of the town of Skar¿ysko-Kamienna, Central Poland) was examined due to intermediate individuals found in sympatric populations of these species. Both putative parents as well as individuals that appeared hybrid-like were found in an extensive, wet hay-meadow. Various vegetative and reproductive characteristics were studied to identify hybrids. Interestingly, Polish access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…A series of recent papers has clarified numerous lower-level taxonomic issues among multiple Eurasian taxa of Agrostis , Calamagrostis and Deyeuxia (many from the far East) and described new species, most not yet included in molecular studies (Paszko and Nobis 2010, Paszko 2011, 2012a, b, 2013, 2014a, b, c, d, e, 2015, 2016, Paszko and Ma 2011, Paszko and Chen 2013, Paszko and Pendry 2013a, b, Paszko and Soreng 2013, Paszko et al 2013, 2015, Nobis et al 2014). In Mexico and Central America, species are treated in Calamagrostis (Beetle 1987, Pohl and Davidse 1994, Peterson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A series of recent papers has clarified numerous lower-level taxonomic issues among multiple Eurasian taxa of Agrostis , Calamagrostis and Deyeuxia (many from the far East) and described new species, most not yet included in molecular studies (Paszko and Nobis 2010, Paszko 2011, 2012a, b, 2013, 2014a, b, c, d, e, 2015, 2016, Paszko and Ma 2011, Paszko and Chen 2013, Paszko and Pendry 2013a, b, Paszko and Soreng 2013, Paszko et al 2013, 2015, Nobis et al 2014). In Mexico and Central America, species are treated in Calamagrostis (Beetle 1987, Pohl and Davidse 1994, Peterson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, not all specimens need to be phenotypically intermediate. Recent studies have shown that morphological characters of hybrids are not always intermediate between those of the parental species, and hybrids show a mosaic of parental, intermediate and extreme characters (Rieseberg 1995, Paszko and Nobis 2010). Specimens belonging to S. manrakica can probably also exhibit wider morphological variability.…”
Section: Methodsmentioning
confidence: 99%
“…Literature: Schmalhausen, 1886;Zapałowicz, 1906;Zapałowicz, 1911;Širjaev & Lavrenko, 1926;Kotov, 1938;Tzvelev, 1965;Prokudin & Druleva, 1972;Prokudin et al, 1977;Sieber, & Murray, 1982;Sutorý, 1993;Soreng, & Terrell, 1997;Kopecký et al, 2006;Bednarska, 2007;Fedoronchuk et al, 2007;Mahelka et al, 2007;Szczepaniak et al, 2007;Bednarska, 2009;Fedoronchuk et al, 2010;Paszko & Nobis, 2010;Tzvelev, 2014;Angelov & Szczepaniak, 2015;Seregin et al, 2015b;Banfi et al, 2017;Cepurīte & Rūrāne, 2017;Banfi, 2018;Bednarska & Nachychko, 2018;Majka et al, 2018;Krasniak, 2019;Paštová et al, 2019;van der Meer, 2019a;Tkach et al, 2020;Chorna et al, 2021;Urfusová et al, 2021;Wilcox et al, 2021;Peterson et al, 2022;Shynder et al, 2022a;Olshanskyi, Potamogeton ×fluitans Roth, Tent. Fl.…”
Section: Stipa ×Majalisunclassified